Improving survival in children with AIDS in Brazil: results of the second national study, 1999-2002 - Luiza Harunari Matida; Alberto Novaes Ramos Jr; Jorg Heukelbach; Adriana Sañudo; Regina Célia de Menezes Succi; Heloisa Helena de Sousa Marques; Marinella Della Negra; Norman Hearst (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
The objective of this study is to characterize survival in children with AIDS diagnosed in Brazil between 1999-2002, compared with the first national study (1983-1998). This national retrospective cohort study examined a representative sample of Brazilian children exposed to HIV from mother-to-child transmission and followed through 2007. The survival probability after 60 months was analyzed by sex, year of birth and death, clinical classification, use of antiretroviral therapy (ART) and prophylaxis for opportunistic diseases. 920 children were included. The survival probability increased: comparing cases diagnosed before 1988 with those diagnosed from 2001-2002 it increased by 3.5-fold (from 25% to 86.3%). Use of ART, initial clinical classification, and final classification were significant (p < 0.001) predictors of survival. Issues regarding quality of records and care were identified. The results point to the success of the Brazilian policy of providing ART. The improvement of clinical status contributes to quality of life, while indicating challenges, particularly practices to improve long-term care.